2(-2p+3)-5(p+7)=34

Simple and best practice solution for 2(-2p+3)-5(p+7)=34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-2p+3)-5(p+7)=34 equation:


Simplifying
2(-2p + 3) + -5(p + 7) = 34

Reorder the terms:
2(3 + -2p) + -5(p + 7) = 34
(3 * 2 + -2p * 2) + -5(p + 7) = 34
(6 + -4p) + -5(p + 7) = 34

Reorder the terms:
6 + -4p + -5(7 + p) = 34
6 + -4p + (7 * -5 + p * -5) = 34
6 + -4p + (-35 + -5p) = 34

Reorder the terms:
6 + -35 + -4p + -5p = 34

Combine like terms: 6 + -35 = -29
-29 + -4p + -5p = 34

Combine like terms: -4p + -5p = -9p
-29 + -9p = 34

Solving
-29 + -9p = 34

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + -9p = 34 + 29

Combine like terms: -29 + 29 = 0
0 + -9p = 34 + 29
-9p = 34 + 29

Combine like terms: 34 + 29 = 63
-9p = 63

Divide each side by '-9'.
p = -7

Simplifying
p = -7

See similar equations:

| -5​4/​g=3 | | 7a-3b+5= | | -34+x=6(-8-x) | | 6x/-4=-.3 | | -23-8x=-2(x-7)-7 | | (y^4/5)^2 | | 7900=40x+4000 | | k-4=-7 | | 3(2x-1)=3-2(x-1) | | 4=22x | | -2.2d+16.95=-3.8d-14.41 | | d/-7-8 | | -18+c=-14 | | differentiate:dy/dx=3x^2 | | f(2.3)= | | [(2x-5)/5]-13-x | | Y=9x-2x^2 | | 0.25r+0.75=0.5r | | 2(z+5)-2z=7 | | 6x+5y-7x-8y+4= | | 3a+4a=31 | | ((2x-5)/5)-13-x | | 12-(7+4)= | | 125=25^3/2 | | -10=5x-2y | | 8(t-5)+4t=6(2t+3)-8 | | 6n-(4n+22)=5-(6n-2) | | 7x-5w+3x+6y+3y+2w= | | 28+19y=8+15y | | 10x-10y=16 | | 6x+15-2x=5.4+23 | | 8n+9=x |

Equations solver categories